2020
DOI: 10.3390/microorganisms8121849
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Strategies to Increase Secondary Metabolite Production from Cyanobacteria

Abstract: Cyanobacteria, given their ability to produce various secondary metabolites utilizing solar energy and carbon dioxide, are a potential platform for sustainable production of biochemicals. Until now, conventional metabolic engineering approaches have been applied to various cyanobacterial species for enhanced production of industrially valued compounds, including secondary metabolites and non-natural biochemicals. However, the shortage of understanding of cyanobacterial metabolic and regulatory networks for atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 210 publications
(94 reference statements)
1
13
0
Order By: Relevance
“…Recent research demonstrated that the production of specialized metabolites is mostly coded by clustered genes on chromosomal DNA rather than by plasmidic DNA. However, the related pathways are still not fully clarified and thus provide a new theoretical frontier for academic researchers in enzymology, control and differentiation [4].…”
Section: Microorganisms and Metabolites: An Incredible World Of Novel...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research demonstrated that the production of specialized metabolites is mostly coded by clustered genes on chromosomal DNA rather than by plasmidic DNA. However, the related pathways are still not fully clarified and thus provide a new theoretical frontier for academic researchers in enzymology, control and differentiation [4].…”
Section: Microorganisms and Metabolites: An Incredible World Of Novel...mentioning
confidence: 99%
“…Metabolic engineered-based approaches are now widely applied to cyanobacteria for the industrial production of value-added compounds, including specific metabolites and non-natural biochemicals. However, the review of Jeong et al (2020) [4] covers a large synthetic and systems biology approach for advanced metabolic engineering of cyanobacteria. This involves an overview of known biosynthetic clusters coding for essential compounds, and knowledge of heterologous expression for cyanobacterial secondary metabolite production.…”
Section: Future Strategies and Perspectivesmentioning
confidence: 99%
“…An important aspect of cyanobacteria is that they produce a wide range of secondary metabolites with diverse chemical structures and biological activities (vitamins, sunscreens, antibiotics, anti-cancer, toxins, etc.) (Cassier-Chauvat, Dive, & Chauvat, 2017;Demay, Bernard, Reinhardt, & Marie, 2019;Jeong et al, 2020;. For instance, at least 800 different secondary metabolites have been identified in marine cyanobacteria so far, a number likely representing a small fraction of the natural product repertoire.…”
mentioning
confidence: 99%
“…Cyanobacteria use about 5-6% of their genome length to direct the production of secondary metabolites. For example, it is predicted that the genome of Moorea producens PAL-8-15-08-1 carries 18 NRPS Biosynthetic Gene Clusters ( Jeong et al, 2020). These gene clusters are often large (Cassier-Chauvat et al, 2017;Dittmann et al, 2015;Pearson et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation